POLITENESS STRATEGIES AND LINGUISTIC POLITENESS MARKERS OF IMPERATIVE IN THE VERY BEST OF DONALD DUCK COMIC SERIES AND THEIR TRANSLATION IN INDONESIAN - Nunun Tri Widarwati (PRASASTI: Journal of Linguistics, 2014)
The present study examines politeness strategies and linguistic politeness markers of English imperative speech acts used in The Very Best of Donald Duck Comics Series. It also identifies the translation techniques applied to translate those markers into Indonesian and evaluate their accuracy and acceptability. The findings indicate that three politeness strategies (bald on record, positive politness and negative politeness) are used and about thirty five linguistic politeness markers are identified and translated in Indonesian using five translation techniques (literal, variation, deletion, borrowing and established equivalence).  The findings also show that the accuracy and acceptability of the translation of linguistic politeness markers are found to be good. Nevertheless, the application of deletion technique tends to distract the pragmatic meaning and force of the linguistic politeness markers in the target language. In such a case, deletion technique should be avoided. Key words: linguistic politeness stretegies, linguistic politeness markers, translation technique, accuracy, acceptability